Analisis faktor-faktor yang mempengaruhi produksi budidaya ikan nila di Kecamatan Singingi Kabupaten Kuantan Singingi - Okrian Weri Putra; Nursiah Chalid; Nobel Aqualdo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine the factors that influence the production of tilapia fish farming in the District Singingi Singingi Kuantan district. The study was measured using a sample of 50 people using a random sampling method. The method of analysis used by the authors in this study is the Cobb-Douglass production function data used are primary data and secondary data from the years 2007-2012. From the analysis, the regression coefficient value of each variable factors that affect the production of tilapia fish farming dalah X1 (number of seeds) of 0.836, X2 (Feed) of 3.475, X3 (land area) of 0.340, X4 (Drugs) amounted to 0.636 and X5 (labor) of 0.073. From the results of research based on the t test (t-test) the factors that influence the production of tilapia fish farming in the District Singingi Regency Kuantan Singingi with α = 1% where the t value of each variable is still X1 = 2.348, X2 = 6.126, X3 = 1.366, = 1.259 X4, X5 = 0.202 with table value (0.025; 44) was 1,680 in the meantime, the F table value (0.05, 5, 44) is 2.43 the factors that influence the production of tilapia fish farming in the District Singingi Regency Kuantan Singingi is the amount of seed and feed. While the value of the coefficient of determination (R2) is 0.903 means that 90.3% of tilapia aquaculture production in Sub Singingi influenced by the independent variable, while the remaining 9.7% is influenced by other factors that are not addressed in this study. From the analysis of the data according to the F test as a whole is known that all factors of production influence the increase in aquaculture production of tilapia in District Singingi Singingi Kuantan district.Keywords: Production of tilapia fish farming, number of seeds, feed, land area, Drugs, Labor.